A study of hematological parameters and requirement of platelet transfusion in dengue fever - L. S., Yashaswini; ., Priya (International Journal of Advances in Medicine, 2017)
Background: Dengue is a common vector-borne disease in India with significant morbidity & mortality. Thrombocytopenia is a common complication in dengue. Bleeding manifestations in dengue put an immense pressure on both patients and treating physicians. There are no clear guidelines for transfusion of platelets in bleeding patients and role of Platelet transfusion in this condition is a bit controversial. Methods: It was an observational study done at Sree Rajarajeswari medical college and hospital between 1st May and 31st July 2016. Total of 100 dengue-positive cases were studied with respect to clinical features, laboratory parameters and requirement of platelet transfusion. Results: Majority of patients were males and in the age group 21-30 years. Fever was present in all cases, with a mean of 3-6 days duration. Epistaxis was the most common bleeding manifestation (43%), Malena being the least (3%). Leucopenia was observed in 52% patients. Thrombocytopenia was seen in 89% of admitted patients and 38% among them had raised aPTT. 53%of patients in our study received platelet transfusion. Conclusions: Bleeding manifestations have no significant association with severity of platelet count. Severe leucopenia is associated with thrombocytopenia. There is no need of platelet-transfusion in all patients with thrombocytopenia with minor bleeds.